Moral absolutes in the New Natural Law Theory: the prohibition of directly damaging a basic human good - Caviedes Thomas, Gabriela Sofía (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
This paper seeks to show how the New Natural Law Theory bases the existence of absolute moral norms, and its importance to moral philosophy. The authors of this theory argue that natural law, through certain moral norms, leads to choose and protect basic human goods, corresponding to multiple aspects of human nature, avoiding its destruction, damage or impeding. Although most of this norms have exceptions according to the circumstances, those negative norms that forbid to choose an action that always directly violates a basic human good are exceptionless, because such actions cannot be compatible with self-fulfillment and attacks human dignity. The division of this work shall be as it follows: in the first four sections, I will make an approach to the key concepts that, for the New Natural Law Theory, explain the truth of exceptionless moral norms; in the fifth, I will show how these authors demonstrate moral absolutes and criticize consequentialism, and in the sixth, I will make a brief critical review of the arguments presented.